O ensino religioso e a gestão escolar na formação ética do educando - Santos, Claudia Maria da Silva (2015)
Within Brazilian Education there is research which presents different approaches regarding the training of Religious Education teachers, but there is a lack of studies about the training of Religious Education teachers with the goal of developing their practice based on school management aimed at the ethical education of the student. Starting from this premise, this research project proposes as its object of study: Religious Education and School Management in the ethical education of the student. These conditions impose issues about management, education and the profile of the Religious Education teacher. The historical trajectory of this teaching as an inheritance of an understanding about the identity of the discipline with regard to school management; the review of its methods based on the presuppositions which are at the foundation of the different theoretical models of School Religious Education and the pointing out of some reflections which can contribute to a specific model for each school universe. Religious Education needs to be inserted in the Political Pedagogical Project so as to guarantee its epistemological and pedagogical foundations so that it may have a clear identity and thus, be understood as an area of knowledge within the school community, based on the education of the student to better comprehend him/her self through the ethical principles so as to go objectively seeking the axis and be able to find him/herself in society, since it is based on ethics as moral conduct that each individual characterizes his/her personality choosing and defining the occupations to which they will dedicate themselves and thus discover themselves. This research paper sought to answer the following question: What is the importance of School Management from a democratic perspective? What is the relation of School Management with Religious Education in the ethical education of the student? The main axis was to identify and analyze School Management based on its epistemology: contextualize Religious Education in the history of Brazilian Education; get to know the education of the teachers; understand ethics from an epistemological point of view and how this can be constructed based on Religious Education supported by school management. The theoretical support is founded on authors who deal with educational methodology, history and educational policies and the education of teachers in a general way, besides authors who deal with ethics. It is a qualitative research with explorative study. Currently Religious Education registers a new reading as to its epistemological conception. So that Religious Education today may meet its goals, public policies of teacher training are needed. Besides this, the research seeks to relate Religious Education with school management based on the teacher s training/education, having as its goal the ethical education of the student. The study can give its social contribution in the organization of these policies pointing out paths to access continuing education of Religious Education teachers allied to Democratic School Management.